Enhancing Rooting and Biomass of Sugarcane Setts with Bio-Stimulant at Germination Stage - Oñal, Jr., Paulino A; Baldonebro, Jessel Jane G.; Cortez, Manuel D.; Andrade, Francis E.; Bermejo, Nathaniel John C.; Lovino, Marinel M.; Poblacion, Anna Mae V. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
The study aims to determine the effect of the application of bio-stimulant to one-eyed and two-eyed sugarcane setts as planting materials in enhancing the rooting and biomass. The study was conducted at UNO-R School of Agriculture, Philippines from November to December 2023. Phil 2006-2289 variety was used as planting materials. The study was laid out in a two-way factorial Completely Randomized Design with the kind of materials as the main plot and the four (4) levels of concentration of bio-stimulant solutions (BSS) plus the control as the sub-plots replicated 4 times. Cane setts preparation was done a day before the planting operations. Leaf sheaths were remove and only those setts with good and viable eye buds were selected for planting. Soaking was done for 24 hours. Bio-stimulants (BSS) were diluted in water and used as a soaking solution and succeeding application was done 15 days after planting. Statistical analysis revealed highly significant differences among treatments on the germination, biomass accumulation, weight and length of roots, number, weight, and height of tillers applied with 500ml of BSS. There was a high significant difference on the root length and biomass as influence by type of cane setts and the levels of concentration of BSS. Two-eyed cane setts applied with 500ml of BSS got the heaviest root weight and biomass. The study recommends the use of 500ml of BSS and two-eyed cane setts in enhancing the rooting and biomass of sugarcane plants during the germination phase.